Survei Sarana dan Prasarana Pendidikan Jasmani di SMP Se-Kecamatan Teluk Pakedai Kabupaten Kubu Raya - Mariska, Revi (Journal Sport Academy, 2025)
Physical Education, Sports, and Health (PJOK) is a subject that plays an important role in developing physical fitness, motor skills, social attitudes, and healthy lifestyles of students. The success of PJOK learning is greatly influenced by the availability of adequate facilities and infrastructure. This study aims to determine the availability, condition, and ownership status of physical education facilities and infrastructure in Junior High Schools (SMP) throughout Teluk Pakedai District, Kubu Raya Regency. The research method used is descriptive quantitative with a survey research form. The subjects of this study were 7 Public Junior High Schools in Teluk Pakedai District. The data collection technique used direct observation with instruments in the form of observation sheets and documentation. The data obtained were analyzed using percentage techniques to describe the condition of physical education facilities and infrastructure in each school. The results of the study indicate that the availability of physical education facilities and infrastructure in Junior High Schools throughout Teluk Pakedai District is generally still uneven, both in terms of quantity and type. The condition of some facilities and infrastructure is in the good category, but some are still found to be damaged and unsuitable for use. The ownership status of physical education facilities and infrastructure is generally owned by the school. Based on the research results, it can be concluded that physical education facilities and infrastructure in junior high schools throughout Teluk Pakedai District, Kubu Raya Regency, require further attention to support the effective and optimal learning process of physical education and health.